FRI0698 Prevotella and alloprevotella species characterize the oral microbiome of early rheumatoid arthritis. (15th June 2017) - Wolff, B; Boutin, S; Lorenz, H-M; Ueffing, H; Dalpke, A; Wolff, D
Abstract : Background: We previously showed that in this early rheumatoid arthritis (ERA) cohort with a mean disease duration of <6 months, a clinically significant loss of clinical attachment loss as surrogate of alveolar bone loss is detectable compared with a matched healthy control cohort (1). Evidence is accumulating that distinct pathogens residing in reservoirs such as the oral cavity, the lung or the gut may play a role in driving the pathogenesis of RA (2–3). Objectives: To characterize the oral microbiome associated with ERA. Methods: 16S amplicon sequencing was used to analyze 88 samples of the supragingival and subgingival microbiome of 22 patients with ERA and 22 matched healthy controls. Oral and periodontal status, clinical activity of ERA and periodontitis, and socio-demographic parameters were used as explanatory variables in the next generation DNA sequencing analysis. Results: Overall, a total of 4.702.161 16S RNA high-quality sequences were yielded. Using a distance-based similarity of >97% for species-level operational taxonomic unit (OTU) assignment, a total of 1054 OTUs were identified (Fig 1 ). The oral microbiota was equally rich and diverse in ERA and control group. Subgingivally, Prevotella oris, Prevotella oralis, Prevotella nigrescens, Alloprevotella rava and Alloprevotella tannerae were associated with early RA independent of severity of periodontitis. Conclusions: Prevotella and Alloprevotella species were enriched in patients with early RA independent of severity of periodontitis. Further studies are needed to test a causal relationship of these species with onset and/or disease progression of RA. References: Oral status in patients with early rheumatoid arthritis: a prospective, case-control study. Wolff B, Berger T, Frese C, Max R, Blank N, Lorenz HM, Wolff D. Rheumatology (Oxford). 2014 Mar;53(3):526–31. The lung microbiota in early rheumatoid arthritis and autoimmunity. Scher JU, Joshua V, Artacho A, Abdollahi-Roodsaz S, Öckinger J, Kullberg S, Sköld M, Eklund A, Grunewald J, Clemente JC, Ubeda C, Segal LN, Catrina AI. Microbiome. 2016 Nov 17;4(1):60. Expansion of intestinal Prevotella copri correlates with enhanced susceptibility to arthritis. Scher JU, Sczesnak A, Longman RS, Segata N, Ubeda C, Bielski C, Rostron T, Cerundolo V, Pamer EG, Abramson SB, Huttenhower C, Littman DR. Elife. 2013 Nov 5. Acknowledgements: Wolff and Boutin contributed equally. Disclosure of Interest: None declared